Asymmetric Hetero‐Diels–Alder Reaction of Danishefsky's Diene with α‐Ketoesters and Isatins Catalyzed by a Chiral N, N′‐Dioxide/Magnesium(II) Complex. Issue 44 (11th September 2014) - Zheng, Jianfeng; Lin, Lili; Fu, Kai; Zhang, Yulong; Liu, Xiaohua; Feng, Xiaoming
Abstract A highly enantioselective hetero‐Diels–Alder reaction of Danishefsky's diene with α‐ketoesters and isatins has been realized by using a chiral N, N′‐dioxide/MgII complex. In the presence of only 0.1–0.5 mol % catalyst, a series of substrates were transformed into the corresponding tetrasubstituted 2, 3‐dihydropyran‐4‐ones in up to 99 % yield and more than 99 % ee in two hours.